To Assess Liability Determination of School Badminton Injury Accidents: an Analysis Framework - Liu Lei,; ChengTe Lin, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In recent years, public concern has intensified regarding the assessment of culpability in school sports-related badminton injuries. Although existing studies have examined liability principles from a legal standpoint, there is a notable lack of research exploring the evolution of culpability determination through the lens of "law and economics." To address this gap, we introduce the evolutionary game model, a pivotal theoretical tool in "law and economics," to investigate the factors influencing the strategic choices of involved parties and to identify the most applicable liability principle for injuries incurred during school athletic events. Our findings indicate a strong correlation between both the costs of accident compensation and prevention and the strategic selection of the responsible party. Furthermore, we demonstrate that while both proportional and strict liability principles can effectively determine fault in school sports injuries, they influence party behaviour differently. Specifically, the proportional liability principle may incentivize schools and students to exercise "appropriate caution" to mitigate the risk of sports-related injuries, in contrast to the strict liability principle.